INFLUENCE OF INTEGRATED FINANCIAL MANAGEMENT INFORMATION SYSTEM (IFMIS) ON THE PERFORMANCE OF GOVERNMENT ENTITIES IN NIGERIA - Salaudeen Ibrahim; Abdul-Hakeem Shuaib; Muhammed Basiru Mustapha; Benuh Adama Idris; Tunde Saka Abdulsalam (Malete Journal of Accounting and Finance)
Public Sector Performance has been a contemporary discourse among researchers in Nigeria. Despite the formidable regulatory and institutional frameworks put in place to strengthen public sector finance management in Nigeria, the domain continues to struggle with huge financial management infractions that are not in tune with the norms as well as international best practices thereby resulting to performance failure. The main objective of this study was to investigate the influence of Integrated Financial Management information System (IFMIS) on performance of government entities’ in Nigeria. The research design deployed was descriptive and inferential mixed research design using a purposive sampling technique. The study population was 1504 comprises of selected top and middle level pool officers in the Accountant-General for the Federation office on grade level 13 to 17. The study’s primary data source sample size was 306 using Krejcie and Morgan, (1970) while the interview sample size was also 3 (three). Primary data was collected using questionnaire and interview while Partial Least Square was used to analyse the quantitative data and Thematic/NVIVO was used to analyse the Qualitative data. Finding from the quantitative analysis shows that a positive statistically significant relationship exist between the two variables as the path model coefficient results indicates that IFMIS is significantly related to both financial (β = 0.466; p< 0.05) and non-financial performance of government entities’ with (β = 0.490; p< 0.001). Finding from the qualitative analysis corroborated with the quantitative findings, its results however, indicates existence of various challenges ranging from infrastructures deficient as well as capacity building issues for IFMIS operators; The study therefore concludes that IFMIS significantly influence both financial and non- financial performance of government entities with limitations of various challenges. The study recommends therefore, that government should endeavour to provide strong Information Technology (IT) infrastructure and the right capacity building of the operators as it is expected to increase the level of performance in entities’, and assist in providing more meaningful information for decision making process.